A Systematic Review of Computational Fluid Dynamics Models in the Stomach and Small Intestine - Palmada N; Hosseini S; Avci R; Cater JE; Suresh V; Cheng LK (MDPI (Basel, Switzerland), 2023)
The use of in silico models to improve our understanding of the fluid dynamics within the gastrointestinal tract has increased over the last few decades. Computational fluid dynamics (CFD) is an in silico technique that can be used to characterize and model the fluid mechanics driving the digestion of food and absorption of nutrients. This systematic review outlines the current methodologies used to develop CFD models of the stomach and small intestine, and summarizes the flow and mixing patterns predicted from these models. A literature search was conducted on Scopus, and 15 stomach CFD studies and 15 small intestine CFD studies were included in this review after the literature selection and exclusion process. Two primary flow patterns; retropulsive flow and recirculation regions, were identified within the stomach CFD models. The flow patterns within the small intestine were depended on the type of motility pattern present. The shortcomings of the current models are discussed, and considerations for future gastric and intestinal flow modeling are provided.
Keywords: computational fluid dynamics; gastric digestion; small intestine; human stomach